Análisis de parámetros de transmisión en sistemas de comunicaciones moleculares mediante diferentes condiciones comunicacionales en la transmisión y recepción - Armas Benavides, Santiago David (2023)
Molecular Communication MCs is one of the most important fields in science due mainly the current applications in the medical field to enhance the patient's health with less invasive treatments. MCs are so important that IEEE (Institute of Electrical and Electronic Engineers) has defined two standards, they are 1906.1 and 1906.1.1, they support to NS-3 (Network Simulator-3) as the software to implement molecular communicational sceneries. Thus, in this work is developed three transmission/reception cases in which are used OOK (On-Off Keying), MoSK (Molecular Shift Keying) and CSK (Concentration Shift Keying) modulations, with receptors of type absorbers, ligands and those defined by concentrations at receiverend, the simulation is contrasted with theoretical equations to confirm results.